LENGTH-WEIGHT RELATIONSHIP IN SAURIDA TUMBIL AND 5. UNDOSQUAMIS AND RELATIVE CONDITION IN S. TUMBIL - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
The length-weight relationship is useful for understanding the mathematicalrelationship between length and weight so that one may be convertedinto another. It is also useful to measure the 'Condition,' i.e., the variation fromexpected weight for length of individual fish or groups of individuals as indicationsof fatness, general 'well being,' gonad development, etc